High-toughness polyether-ether-ketone composite material as well as preparation method and application thereof
By synergistically modifying polyether ether ketone with graphene oxide and silicone rubber, a high-strength and tough polyether ether ketone composite material was prepared, which solved the problem that existing materials could not take into account both high strength and high toughness, and achieved high strength and high thermal stability of the material and high toughness.
Patent Information
- Application Number
- CN202411538046.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing polyether ether ketone composites cannot take into account high strength and high toughness. Traditional toughening materials will sacrifice the strength and heat resistance of the material when improving toughness.
High strength and tough polyether ether ketone composite material was prepared by mixing and grinding graphene oxide, silicone rubber and polyether ether ketone resin powder, oscillating and mixing through a vortex mixer, and then pressing and sintering at room temperature.
It has achieved the strongness of the polyether etherketone composite without reducing the strength and thermal stability of the matrix material, with the tensile strength not less than 100MPa, the fracture energy is ≥500J/m3, the Td5 is 575.46℃, and the residual at 800℃. The amount is 50.8%.
Smart Images

Figure CN119432037A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyetheretherketone composite materials, and particularly relates to a high-strength and tough polyetheretherketone composite material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of aerospace, aviation, automobile industry, biomedicine and other fields, the demand for high-performance materials has increased, especially the emergence of high-performance fiber-reinforced thermoplastic composites, which has filled the urgent demand for high-performance materials in cutting-edge fields. Polyetheretherketone (PEEK) is a polymer composed of repeating units containing one ketone bond and two ether bonds in the main chain structure. It is a special polymer material. Compared with other special engineering plastics, it has more significant advantages, such as high temperature resistance of 260°C, excellent mechanical properties, good self-lubrication, chemical corrosion resistance, flame retardancy, peeling resistance, wear resistance, radiation resistance, etc. Its super mechanical properties make it suitable for high-end machinery, automobiles, nuclear engineering and aviation.
[0003] Polyetheretherketone has rigidity and flexibility, especially its fatigue resistance under alternating stress is very outstanding, which is comparable to alloy materials. While traditional rubber toughening materials have good toughening effects, they often sacrifice the strength and heat resistance of the material, and cannot meet the requirements of polyetheretherketone materials for toughness and high temperature resistance; in addition, although rigid particle toughening can simultaneously improve the toughness and strength of plastic polymers, its improvement in toughness is limited. Therefore, how to significantly improve the toughness of polyetheretherketone without reducing its original strength and heat resistance is an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problem that the existing polyetheretherketone composite materials cannot have both high strength and high toughness, and to provide a high-strength and toughness polyetheretherketone composite material and a preparation method and application thereof.
[0005] One of the purposes of the present invention is to provide a method for preparing a high-strength and tough polyetheretherketone composite material, the method being carried out according to the following steps:
[0006] S1: Graphene oxide, silicone rubber and polyetheretherketone resin powders are mixed and ground, and then put into a centrifuge tube and oscillated and mixed by a vortex mixer to obtain a mixed powder;
[0007] S2: The mixed powder is pressed at room temperature and then sintered to obtain a high-strength and tough polyetheretherketone composite material.
[0008] It is further defined that the mass ratio of graphene oxide, silicone rubber and polyetheretherketone resin powder in S1 is 0.1:(0.1-0.15):(8-10).
[0009] It is further defined that the mixing and grinding in S1 is performed for 15-20 minutes.
[0010] Furthermore, the S1 was shaken and mixed 3-5 times, each time for 5-8 minutes.
[0011] It is further defined that the pressing pressure in S2 is 3-6 MPa and the pressing time is 3-5 min.
[0012] It is further defined that the sintering temperature in S2 is 390-400°C and the sintering time is 40-45 minutes.
[0013] It is further defined that after the sintering in S2 is completed, the mold is cooled along with the temperature of the oven, and the oven temperature is opened after it is cooled to 140-160°C, and the mold is cooled to room temperature along with the mold.
[0014] The second object of the present invention is to provide a high-strength and tough polyetheretherketone composite material prepared by the above method, wherein the polyetheretherketone composite material has a tensile strength of not less than 100MPa and a fracture energy of ≥500J / m 3 .
[0015] It is further defined that the polyetheretherketone composite material has a crystallinity of ≤25%.
[0016] The third object of the present invention is to provide a high-strength and tough polyetheretherketone composite material prepared by the above method for use in aerospace, automotive industry, and biomedical fields.
[0017] Compared with the prior art, the present invention has the following significant effects:
[0018] The present invention uses silicone rubber and graphene oxide to synergistically modify polyetheretherketone. By selecting and matching the modified materials, the synergistic effect of silicone rubber and graphene oxide is fully exerted. While not reducing the strength and thermal stability of the base material, the toughness is greatly improved. When the sample is prepared according to the ASTM D638 standard, the tensile strength is not less than 100MPa, and the fracture energy is ≥500J / m 3 , T d5 It is 575.46℃, and the residual amount at 800℃ is 50.8%. It can be seen that the obtained polyetheretherketone composite material has high strength, high thermal stability and high toughness, and can be used in aerospace, automotive industry, biomedicine and other fields with high requirements on comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD spectra of pure PEEK and its composite materials obtained in Example 1 and Comparative Examples 1-3;
[0020] Figure 2is the flexural strength of pure PEEK and its composite materials obtained in Example 1 and Comparative Examples 1-3 according to ASTM D790 standard;
[0021] Figure 3 is the tensile strength of pure PEEK and its composite materials obtained in Example 1 and Comparative Examples 1-3 according to ASTM D638 standard;
[0022] Figure 4 is the tensile fracture absorption energy of pure PEEK and its composite materials obtained in Example 1 and Comparative Examples 1-3;
[0023] Figure 5 The thermal weight loss curves of pure PEEK and its composite material obtained in Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0026] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0027] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0029] The silicone rubber SR described in the following examples was purchased from German Wacker silicone resin 604.
[0030] The polyetheretherketone resin powder described in the following examples was purchased from Jilin Zhongyan Polymer Materials.
[0031] Embodiment 1: The preparation method of the high-strength and tough polyetheretherketone composite material of this embodiment is carried out according to the following steps:
[0032] 0.1g of graphene oxide GO, 0.1g of silicone rubber SR and 9.8g of polyetheretherketone resin powder were mixed and ground in a mortar for 15 minutes, and then the ground blend was placed in a centrifuge tube and oscillated and mixed by a vortex mixer for 3 times, each time for 5 minutes. The powder mixture was then filled into a mold coated with a release agent, and a small flat vulcanizer was used to pressurize 5MPa at room temperature for 5 minutes. Finally, the mold was placed in an electric oven, heated to 395℃ and kept warm for 40 minutes, then the power was turned off, and the mold was allowed to cool with the temperature of the oven. The oven temperature dropped to 150℃ and then the box was opened. The mold was cooled to room temperature and demolded to obtain a high-strength and tough polyetheretherketone composite material, recorded as GO / SR / PEEK.
[0033] Comparative Example 1: The preparation method of polyetheretherketone in this comparative example is carried out according to the following steps:
[0034] 10g of polyetheretherketone resin powder was filled into a mold coated with a release agent, and a small flat vulcanizer was used to pressurize the mold at room temperature to 5MPa for 5min. Finally, the mold was placed in an electric oven, heated to 395℃ for 40min, and then the power was turned off to allow the mold to cool with the temperature of the oven. The oven temperature was cooled to 150℃ before the mold was opened. The mold was cooled to room temperature and demolded to obtain polyetheretherketone, which was recorded as pure PEEK.
[0035] Comparative Example 2 The preparation method of the polyetheretherketone composite material of this comparative example is carried out according to the following steps:
[0036] 0.2g of graphene oxide GO and 9.8g of polyetheretherketone resin powder were mixed and ground in a mortar for 15 minutes, and then the ground blend was placed in a centrifuge tube and oscillated and mixed by a vortex mixer for 3 times, each time for 5 minutes. The powder mixture was then filled into a mold coated with a release agent, and a small flat vulcanizer was used to pressurize 5MPa at room temperature for 5 minutes. Finally, the mold was placed in an electric oven, heated to 395℃ and kept warm for 40 minutes, then the power was turned off, and the mold was allowed to cool with the temperature of the oven. The oven temperature dropped to 150℃ and then the box was opened. The mold was cooled to room temperature and demolded to obtain a polyetheretherketone composite material, recorded as GO / PEEK.
[0037] Comparative Example 3: The preparation method of the polyetheretherketone composite material of this comparative example is carried out according to the following steps:
[0038] 0.2g of silicone rubber SR and 9.8g of polyetheretherketone resin powder were put into a mortar and mixed for 15 minutes. The ground blend was then placed in a centrifuge tube and mixed by vortex mixer for 3 times, each time for 5 minutes. The powder mixture was then filled into a mold coated with a release agent, and a small flat vulcanizer was used to pressurize 5MPa at room temperature for 5 minutes. Finally, the mold was placed in an electric oven, heated to 395°C for 40 minutes, and then the power was turned off to allow the mold to cool with the temperature of the oven. The oven temperature was cooled to 150°C before opening the box. The mold was cooled to room temperature and demolded to obtain a polyetheretherketone composite material, recorded as SR / PEEK.
[0039] Figure 1 This is the XRD spectrum of pure PEEK and its composites. Pure PEEK has four main diffraction peaks at (110), (111), (200) and (211), corresponding to 2θ positions of 18.88°, 20.87°, 22.86° and 28.90°, respectively, indicating its orthorhombic structure. All composite materials show the main diffraction peaks similar to the orthorhombic phase of PEEK, and there is no obvious position change, indicating that with the addition of GO and SR, the crystal structure of PEEK remains unchanged. Through the calculation and analysis of the curves, it is concluded that the crystallinity of pure PEEK, GO / PEEK, SR / PEEK and GO / SR / PEEK composites are 28.82%, 26.33%, 25.99% and 24.64%, respectively.
[0040] The obtained composite materials were sampled and tested according to ASTM D790 standard. Figure 2 For the comparison of the flexural strength of pure PEEK and its composite materials, the flexural strength of PEEK is 173.0 MPa, the flexural strength of GO / PEEK is 189.0 MPa, the flexural strength of SR / PEEK is 176.1 MPa, and the flexural strength of GO / SR / PEEK is 179.2 MPa.
[0041] The obtained composite materials were sampled and tested according to ASTM D638 standard. Figure 3 For the comparison of the tensile strength of pure PEEK and its composite materials, the tensile strength of PEEK is 83.8 MPa, the tensile strength of GO / PEEK is 89.8 MPa, and the tensile strength of SR / PEEK is 91.01. The tensile strength of GO / SR / PEEK increases from 83.8 MPa to 104.7 MPa.
[0042] Figure 4 It is the fracture energy of the composite material calculated based on the tensile specimen, which is used to judge the toughness of the material. The fracture energy of pure PEEK is 176.9 J / m 3In comparison, the fracture energies of GO / PEEK and SR / PEEK are 248.4 J / m 3 and 438.6 J / m 3 , while the fracture energy of GO / SR / PEEK is 501.9 J / m 3 Compared with pure PEEK, the increases were 35.9%, 129.1% and 174.53%. This proves that the toughness of GO / SR / PEEK composites is improved without reducing the strength of the matrix material. GO and SR have a synergistic effect.
[0043] High thermal stability is the main reason why PEEK resin has become a popular candidate for composite polymer matrix. Therefore, it is most important not to improve mechanical properties at the expense of thermal properties. Therefore, the material was subjected to thermogravimetric analysis (TGA) in the range of 25-800 °C under nitrogen conditions with a heating rate of 10 °C / min. Figure 5 The TGA curves of pure PEEK and GO / SR / PEEK composites are shown. The temperature at which pure PEEK loses 5% of its weight (T d5 ) is 566.5℃, and the residual content at 800℃ is 48.0%. After adding GO and SR to PEEK, T d5 The temperature of the composite material is 575.46℃, and the residual amount at 800℃ is 50.8%, which is 2.8% higher than that of PEEK. This shows that the composite material still has high thermal stability.
[0044] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-strength and tough polyetheretherketone composite material, characterized in that: The method is carried out according to the following steps: S1: Graphene oxide, silicone rubber and polyetheretherketone resin powders are mixed and ground, and then put into a centrifuge tube and oscillated and mixed by a vortex mixer to obtain a mixed powder; S2: The mixed powder is pressed at room temperature and then sintered to obtain a high-strength and tough polyetheretherketone composite material.
2. The method according to claim 1, characterized in that The mass ratio of graphene oxide, silicone rubber and polyetheretherketone resin powder in S1 is 0.1:(0.1-0.15):(8-10).
3. The method according to claim 1, characterized in that Mix and grind in S1 for 15-20 min.
4. The method according to claim 1, characterized in that: The mixture was shaken in S1 for 3-5 times, each time for 5-8 min.
5. The method according to claim 1, characterized in that The pressing pressure in S2 is 3-6 MPa and the pressing time is 3-5 min.
6. The method according to claim 1, characterized in that The sintering temperature in S2 is 390-400°C and the sintering time is 40-45 minutes.
7. The method according to claim 1, characterized in that After sintering in S2 is completed, the mold is cooled along with the temperature of the oven. After the oven temperature drops to 140-160°C, the box is opened and the mold is cooled to room temperature.
8. The high-strength and tough polyetheretherketone composite material prepared by the method according to any one of claims 1 to 7, characterized in that: According to ASTM D638 standard, the tensile strength is not less than 100MPa and the fracture energy is ≥500J / m 3 .
9. The method composite material according to claim 8, characterized in that Crystallinity ≤25%.
10. Application of the high-strength and tough polyetheretherketone composite material prepared by the method according to any one of claims 1 to 7 in the fields of aerospace, automobile industry, and biomedicine.
Citation Information
Patent Citations
Iron oxide-modified graphene-silicone rubber composite and preparation method thereof
CN105985645A
Graphene oxide-enhanced polyether-ether-ketone composite material and preparation method thereof
CN109320904A
Polysiloxane / graphene oxide nano composite material for modifying silicon rubber and modification method thereof
CN109504099A
Toughening filler based on graphene oxide, preparation method of toughening filler and application of toughening filler in modified polyether-ether-ketone
CN117777476A
Polymer Powder and Method of Preparing the Same
US20200087487A1